The Regulation of Pulmonary Vascular Tone by Neuropeptides and the Implications for Pulmonary Hypertension - Lo, Charmaine C. W.; Moosavi, Seyed M.; Bubb, Kristen J. (Frontiers in Physiology, 2018)
Pulmonary hypertension (PH) is an incurable, chronic disease of small pulmonary vessels. Progressive remodelling of the pulmonary vasculature results in increased pulmonary vascular resistance (PVR). This causes secondary right heart failure. PVR is tightly regulated by a range of pulmonary vasodilators and constrictors. Endothelium-derived substances form the basis of most current PH treatments. This is particularly the case for pulmonary arterial hypertension. The major limitation of current treatments is their inability to reverse morphological changes. Thus, there is an unmet need for novel therapies to reduce the morbidity and mortality in PH. Microvessels in the lungs are highly innervated by sensory C fibres. Substance P and calcitonin gene-related peptide (CGRP) are released from C-fibre nerve endings. These neuropeptides can directly regulate vascular tone. Substance P tends to act as a vasoconstrictor in the pulmonary circulation and it increases in the lungs during experimental PH. The receptor for substance P, neurokinin 1 (NK1R), mediates increased pulmonary pressure. Deactivation of NK1R with antagonists, or depletion of substance P prevents PH development. CGRP is a potent pulmonary vasodilator. CGRP receptor antagonists cause elevated pulmonary pressure. Thus, the balance of these peptides is crucial within the pulmonary circulation (Figure 1). Limited progress has been made in understanding their impact on pulmonary pathophysiology. This is an intriguing area of investigation to pursue. It may lead to promising new candidate therapies to combat this fatal disease. This review provides a summary of the current knowledge in this area. It also explores possible future directions for neuropeptides in PH.